ANALISIS EFEK SAMPING JANGKA PANJANG PENGGUNAAN ANTASIDA KALSIUM KARBONAT: NARRATIVE REVIEW - Ridwan, Heri; Aliviani, Arvi; Febriyanti, Ine; Nathania, Levina Nabila; Ramadhan, Muhammad Gilang; Ramadani, Nur Oktavia; Maharani, Syifa Anisa (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
The widespread use of calcium carbonate antacids in self-medication is often considered safe, but excessive consumption and long-term use can cause serious side effects that affect various body systems. This study aims to analyze the long-term side effects of calcium carbonate based on the latest scientific evidence. The method used was a narrative review by selecting relevant articles from PubMed, ScienceDirect, and Google Scholar through inclusion and exclusion criteria, resulting in six main articles for analysis. The results showed that prolonged use of CaCO₃ can cause progressive hypercalcemia, which has the potential to develop into Milk-Alkali Syndrome, characterized by hypercalcemia, metabolic alkalosis, and impaired kidney function. Further complications reported include nephrolithiasis, acute pancreatitis, metabolic disorders, and progressive renal dysfunction. In addition, CaCO₃ is known to interfere with the absorption of various drugs through chelation and changes in gastric pH, thereby potentially reducing the effectiveness of therapy. In conclusion, long-term use of calcium carbonate antacids without adequate monitoring can pose significant health risks, making education and supervision of antacid use essential to prevent toxicity and harmful drug interactions.